Avaliação da resistência à insulina e da adiponectinemia no prolactinoma - Lilian Freitas de Assunc?o Alves Rodrigues (2011)
Prolactin (PRL) is a multifunctional hormone secreted by the lactotroph cells of the pituitary whose receptors are located in several tissues. Prolactinomas are pituitary adenomas that produce and secrete PRL. Hyperprolactinemia is associated to obesity, insulin resistance and endothelial dysfunction. The control of PRL levels improves the metabolic parameters. Insulin resistance is the inability to exert its numerous actions, despite the preserved beta cells secretion, and it can be measured by the homeostasis model assessment of insulin resistance (HOMA-IR). Adiponectin is a protein secreted mainly by adipocytes whose values are reduced in the obesity and insulin resistance. Its low levels are related to the increased risk of developing diabetes. Evidence suggests that PRL inhibits the adiponectin secretion. Low adiponectin levels were seen during pregnancy and lactation, however, data of patients with prolactinoma are still poor. The purpose of this dissertation was to assess the metabolic changes related to insulin resistance and the adinopectin levels in the prolactinoma and compare with healthy controls (CG) matched for age, gender and body mass index (BMI). A cross-sectional evaluation of 40 patients with prolactinoma, selected from Division of Endocrinology at the Hospital of Clinics of the Federal University of Minas Gerais, between July 2008 and May 2010. All study subjetics provided the free and informed consent document before enrollment. Patients with prolactinoma were divided into two groups: a) 20 with uncontrolled prolactinoma (UPRL), defined as hiperprolactinemia symptoms and high PRL levels; b) 20 with controlled prolactinoma (CPRL), defined as no hyperprolactemia symptoms and normal PRL levels in the last six months. The variable were as follows: body mass index (BMI), waist circumference (WC), waist/hip ratio (WHR), blood pressure (BP), lipid profile (total cholesterol, TC; LDL cholesterol, LDL-c; HDL cholesterol, HDL-c, and triglycerides, TG), HOMA-IR, adiponectin and metabolic syndrome. There was no statistical difference concerning age, gender, BMI, BP, TC and LDL-c between the groups. The variables WC, WHR, TG, HOMA-IR and metabolic syndrome were significantly higher in the UPRL group and the HDL-c and adiponectin levels were significantly lower in the UPRL group. The PRL levels were 211,42±45,66, 15,69±2,45 and 13,74±1,08 ng/mL for UPRL, CPRL and CG, respectively (P<0,05 for UPRL vs. CPRL and CG). The HOMA-IR was 2,69±0,43, 1,20±0,19 and 1,16±0,16 mmol/L x !U/mL for UPRL, CPRL and CG, respectively (P<0,05, UPRL vs. CPRL and CG). The adiponectin levels were 5,78±0,78, 10,13±0,90 and 17,46±1,40 !g/mL for UPRL, CPRL and CG, respectively (P<0,01 for all the comparisons). The analysis of correlations showed that the adiponectin levels are inversely correlated with PRL and HOMA-IR (P<0,01). The conclusion was that the hiperprolactinemia in uncontrolled prolactinomas is associated to the insulin resistance. Controlled prolactinomas have similar HOMA-IR levels to those found in healthy subjects, but still show lower adiponectin levels. These data altogether suggest that prolactinomas are per se a condition associated with decreased adiponectin levels, which may be aggravated by insulin resistance when higher prolactin levels are achieved in noncontrolled patients